If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 6 + -9x = 2 + -1y + -15 Reorder the terms: 6 + 8x + -9x = 2 + -1y + -15 Combine like terms: 8x + -9x = -1x 6 + -1x = 2 + -1y + -15 Reorder the terms: 6 + -1x = 2 + -15 + -1y Combine like terms: 2 + -15 = -13 6 + -1x = -13 + -1y Solving 6 + -1x = -13 + -1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = -13 + -6 + -1y Combine like terms: 6 + -6 = 0 0 + -1x = -13 + -6 + -1y -1x = -13 + -6 + -1y Combine like terms: -13 + -6 = -19 -1x = -19 + -1y Divide each side by '-1'. x = 19 + y Simplifying x = 19 + y
| 8-10p+4+8p= | | z(3+2i)=iz+2 | | 2(x+5)+5=2x+9 | | 3x-250=2858 | | 2x+15=385/(x+1) | | 3x+54-3x+6x+4(54-3x)= | | (x+3)(x^2+2x+6)=0 | | 1/16x-3/4y=-1 | | 5b-3/3b-4b+1/5b | | .2y+.5x=4.05 | | 2/3n=-18 | | -12=.5x+x | | 3y+x=54 | | 2(x+8)=30+18 | | 3x+y=54 | | 4x+4x=50 | | -12=6+1y | | A=5H(b+B) | | 3(2x+8)=30+18 | | 5(11+7)=x | | 3x+y+6x+4y=180 | | x^2-12x+68=0 | | 16x-3[4x+7]=6x-[2x+21] | | 3x+x=372 | | z-7z=5z-3-z | | y^2-20=0 | | x^2-2x+10=58 | | 4v/v-3-3/v-3=7 | | -20+5=1 | | (x^2/2)+9x-2=0 | | 3(x+3)+9=3x+9 | | (x^2/2)+9x-2 |